Effect of Swimming Free 50 Meters for Males on Calcium Levels and Some Enzymes of Thyroid and Parathyroid Gland - Gorgees, Shatha Hazim (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aimed to investigate the effect of swimming free 50 meters on calcium levels and activities of some key enzymes involved in calcium metabolism in males. Materials and Methods. Eleven healthy male adults were selected to participate in the study. They freely swam 50 meters daily for four weeks. A one-group pretest-posttest design was used to evaluate the effect of the swimming intervention on markers of calcium metabolism. Measurements were taken for participants before and after swimming. Fasting blood samples were collected before and after swimming to measure serum calcium levels as well as the activities of alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), 5'-nucleotidase, thyroid stimulating hormone (TSH) and parathormone (PTH) by standard enzymatic methods. Results. After four weeks of swimming free 50 meters daily, serum calcium levels showed a statistically significant increase compared to baseline (p < 0.05). The activities of ALP, AST, and ALT were significantly higher post-intervention (p < 0.05 for all enzymes). There were no significant changes in 5'-nucleotidase, TSH, and PTH activities. Conclusions. The results indicate that swimming free 50 meters daily for four weeks increases serum calcium levels, likely through enhanced bone resorption as suggested by the elevated activities of ALP, AST, and ALT. However, there were no significant effects on thyroid and parathyroid functions as assessed by TSH and PTH.